(3TQM GdMGhj GdUZjQs - (3GdbRhjfj , fLe GdOjf YHO GdZaGQ Hf YHO GdcjQe GdbRhjfj,J (B665 (3g` s
(3ChdgG (B:s
(3HGH bhdg jUM hUjI GdMQ(B: (3Ci jUHM hUjI GdMQ Gdecda s
(3BNQgG (B:s
(3aCeG Ef CYSQ GdTQjcGf KHJ GdESJjdGO ai cd fUa deGdc hKHJ GdhdGA HjfgeG HGdShjI hGddg CYde HGdUhGH Je GdcJGH s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG ebGHdGJ hJUMjMGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B31 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B267s
Keywords: (3CUhd Gdabgs